A comparative analysis of fruit fly and human glutamate dehydrogenases in Drosophila melanogaster sperm development - Vedelek, Viktor; Vedelek, Balázs; Lőrincz, Péter; Juhász, Gábor; Sinka, Rita (Frontiers in Cell and Developmental Biology, 2023)
Glutamate dehydrogenases are enzymes that take part in both amino acid and energy metabolism. Their role is clear in many biological processes from neuronal function to cancer development. The putative testis-specific Drosophila glutamate dehydrogenase, Bb8 is required for male fertility and the development of mitochondrial derivatives in spermatids. Testis-specific genes are less conserved and could gain new functions, questioning whether Bb8 has retained its original enzymatic activity. We show that while Bb8 displays glutamate dehydrogenase activity, there are significant functional differences between the housekeeping Gdh and the testis-specific Bb8. Both human GLUD1 and GLUD2 can rescue the bb8 ms mutant phenotype, with superior performance by GLUD2. We also tested the role of three conserved amino acids observed in both Bb8 and GLUD2 in Gdh mutants, which showed their importance in glutamate dehydrogenase function. The findings of our study indicate that Drosophila Bb8 and human GLUD2 could be a novel example of convergent molecular evolution. Furthermore, we investigated the importance of glutamate levels in mitochondrial homeostasis during spermatogenesis by ectopic expression of the mitochondrial glutamate transporter Aralar1, which caused mitochondrial abnormalities in fly spermatids. The data presented in our study offers evidence supporting the significant involvement of glutamate metabolism in sperm